LGBT in Legal and Criminology Aspects - Umi Sofwatin; Dian Alfiani; Nida Nurjanah; Sintha Dwi Mukti (Universitas Negeri Semarang, 2019)
The LGBT which is an acronym for Lesbian, Gay, Bissexual and Transgender is a group consisting of people who have sexual orientation deviations, behavioral deviations and appearances that are not in accordance with their gender. The current LGBT phenomenon has experienced rapid development in everyday life. LGBT as a form of sexual deviation, behavioral irregularities and appearance that is not in accordance with their gender, has expanded to a society with a normal social order, even these LGBT actors are not only teenagers and adults but also children. Most LGBT people present themselves as heterosexual people, this is done so that LGBT people can get along comfortably in carrying out various social activities in the community. The deviation itself does not rule out the possibility of being in campus life and the perpetrators are students to lecturers. The proliferation of television coverage of LGBT has also expanded the movement of LGBT people to show their identity that they exist. This report will discuss the observations of LGBT communities on campus (UNNES) and how they relate to crimonology and victimology.